Epimerization-free access to C-terminal cysteine peptide acids, carboxamides, secondary amides, and esters via complimentary strategies. Issue 2 (16th November 2017) - Arbour, Christine A.; Kondasinghe, Thilini D.; Saraha, Hasina Y.; Vorlicek, Teanna L.; Stockdill, Jennifer L.
Abstract : We present a convenient method for the diversification of peptides bearing cysteine at the C-terminus that proceeds to form a variety of carboxylic acid, carboxamide, 2° amide, and ester terminated peptides without any detectable epimerization of the α-stereocenter. Abstract : C-Terminal cysteine peptide acids are difficult to access without epimerization of the cysteine α-stereocenter. Diversification of the C-terminus after solid-phase peptide synthesis poses an even greater challenge because of the proclivity of the cysteine α-stereocenter to undergo deprotonation upon activation of the C-terminal carboxylic acid. We present herein two general strategies to access C-terminal cysteine peptide derivatives without detectable epimerization, diketopiperazine formation, or piperidinylalanine side products.